Heat treatment for insect control : developments and applications - Hammond, David (Woodhead Publishing in food science, technology, and nutrition, 2015)
Stored product insects and other pests represent a major hygiene and safety issue to many industries, from food production to building infestation, and issues for timber pallets and packaging. Beds bugs are rapidly becoming a public health issue in hotels, hostels and houses in many parts of the world. While fumigation has been one of the prevalent routes for pest control, there remain issues with the toxicity of the chemicals used and potential exposure to humans therefore heat treatment has proven to be a successful alternative when used correctly. It is well known that excessive heat is.